Reciprocal Learning for listening comprehension - Macias-Silva, Evelyn Carolina; Aquino-Rojas, Marco Antonio; Heredia-Arboleda, Edgar Eduardo; Lara-Velarde, Adriana Carolina (Dominio de las Ciencias, 2021)
Reciprocal learning involves the interaction of students while working with their peers. Thus, it is the objective of this article to present the advantages and implications of reciprocal learning applied to listening comprehension. In addition, it presents the application Liu and Bu´s study, applied to our context. Methodologically, a bibliographic review was carried out, delving into previous studies carried out on the subject and the importance of listening for the acquisition of other communication skills such as writing, reading and speaking. Finally, it is concluded that there is a gap in the research that involves listening comprehension and that reciprocal learning has very broad advantages.